Reading Interest of Senior High School Students: A Case Study - Umi Rachmawati (Universitas Pendidikan Mandalika, 2018)
Nowadays, the development of the teaching and learning of English as a foreign language has been transformed. Learners do not only focus on the learning of speaking and writing but also reading since they are required to be able to smartly respond to the texts they are reading. The development of the information and technology forces the focus of teaching and learning on the critical reading that might be less interesting for the students. The students may not know their interest in reading before they start reading. A unique condition in Magelang regency, a small town close to Yogyakarta, the students of senior high schools have achieved their best achievement for their learning that can be seen from the rank of the school that becomes the best school in terms of the final examination in Central Java. To know the teaching and learning of English in that school can be an alternative for other schools. Based on the case study conducted in some schools in Magelang regency, it can be found that the teaching and learning are still varied. The findings were discussed under the following terms; students’ reading activities, mastery of reading skills, reading materials, and reading modality. It is a problem for the success of language teaching as the students can have low motivation in reading if the reading materials were not interesting for them.